2015
DOI: 10.1371/journal.pone.0140634
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Gene FOKI Polymorphism Contributes to Increasing the Risk of HIV-Negative Tuberculosis: Evidence from a Meta-Analysis

Abstract: BackgroundVitamin D receptor (VDR) gene FokI polymorphism have been studied in relation to tuberculosis (TB) in many populations and provided inconsistent results. In this study, we carried out a meta-analysis to derive a more reliable assessment on FokI polymorphism and the risk of HIV-negative TB.MethodsThe Embase, PubMed, and Cochrane Library databases were used to undertake a comprehensive systematic literature review of all current published VDR gene FOKI association studies aimed at the risk of TB up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…Indeed, HIV infection is associated with a greater risk for disease than HIV-negative individuals. 57 Of note, a study by Xu et al 58 also focused on this topic; nevertheless, our study is more comprehensive than this study and we found the risk effect only in HIV-negative TB patients but not observed in HIV-positive or not clearly identified group. Therefore, our results suggest it is crucial to avoid selection bias in such genotype association studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, HIV infection is associated with a greater risk for disease than HIV-negative individuals. 57 Of note, a study by Xu et al 58 also focused on this topic; nevertheless, our study is more comprehensive than this study and we found the risk effect only in HIV-negative TB patients but not observed in HIV-positive or not clearly identified group. Therefore, our results suggest it is crucial to avoid selection bias in such genotype association studies.…”
Section: Discussioncontrasting
confidence: 56%
“…As demonstrated above, meta-analyses are often used to address inconsistencies among studies. For example, meta-analyses demonstrated an association of a polymorphism in VDR in HIV-negative TB patients (Huang et al 2015 ; Xu et al 2015 ). However, even results from meta-analyses can be mixed, particularly for HLA-DRB1 , with some alleles conferring protection and others susceptibility depending on the population studied (Tong et al 2015 ; Yang et al 2016 ).…”
Section: Host Genetic Susceptibility To Bacterial Infectionmentioning
confidence: 99%
“… 5 , 6 A recent meta-analysis suggested that VDR FokI polymorphism contributes to increasing the risk of pulmonary tuberculosis in human immunodeficiency virus-negative individuals, especially in the Asian region. 7 FokI polymorphism in VDR gene has also been shown to be associated with the susceptibility to spinal tuberculosis in Chinese Han population. 8 We selected VDR ApaI and TaqI genes, for our study, because both these genes are relatively less well studied in spinal tuberculosis.…”
Section: Introductionmentioning
confidence: 99%